2008
DOI: 10.1183/09031936.00129907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhaled human insulin on airway lining fluid composition in adults with diabetes

Abstract: Inhaled human insulin (Exubera1 (human insulin of rDNA origin) Inhalation Powder) causes small, early and reversible changes in pulmonary function in subjects with diabetes mellitus. The present study assessed whether changes occur in cellular and soluble constituents of airway lining fluid consistent with inflammation as a possible cause for Exubera1-associated lung function alterations.Two 31-week, open-label, sequential design phase 2 studies were conducted, one with 20 subjects with type 1 and one with 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…21 In the present analysis, baseline-adjusted concentrations of free and total insulin after 12 weeks of EXU therapy are compared with concentrations after 12 weeks of…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…21 In the present analysis, baseline-adjusted concentrations of free and total insulin after 12 weeks of EXU therapy are compared with concentrations after 12 weeks of…”
Section: Methodsmentioning
confidence: 99%
“…21 In brief, the study included subjects with type 1 diabetes mellitus (T1DM) between 18 and 55 years of age and subjects with type 2 diabetes (T2DM) between 30 and 55 years of age. Patients had to have normal DL CO , total lung capacity, forced vital capacity (FVC), and FEV 1 , [22][23][24] and an FEV 1 /FVC ratio of >70%.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the treatment in several studies non-inflammatory related changes of the lung function were observed and additionally coughing after the treatment was an often observed side-effect [52]. While the lung provides a large surface area for micro-and nano-particles uptake the drug-particle surface will be changed by proteins and lipids from lung surfactant as it was observed for NPs [53].…”
Section: Inhalative or Nasal Insulin Deliverymentioning
confidence: 99%